Altering the availability or proximity of food, alcohol and tobacco products to change their selection and consumption - Hollands, GJ; Carter, P; Shemilt, I; Marteau, TM; Jebb, SA; Higgins, J; Ogilvie, D (Wiley-Blackwell, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: 1. To assess the impact of altering the availability or proximity of: a) food products (including non-alcoholic beverages); b) alcohol products; and c) tobacco products on their selection or consumption. 2. For each of the above products, to assess the extent to which the impact of such interventions is modified by: i) study characteristics; ii) intervention characteristics; and iii) participant characteristics.
Keywords: 4206 Public Health; 42 Health Sciences; Tobacco; Alcoholism, Alcohol Use and Health; Behavioral and Social Science; Nutrition; Substance Misuse; Underage Drinking; Tobacco Smoke and Health; Pediatric; 3.5 Resources and infrastructure (prevention); 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; Oral and gastrointestinal; Cardiovascular; Cancer; Stroke; 3 Good Health and Well Being